2023
DOI: 10.1039/d3md00352c
|View full text |Cite
|
Sign up to set email alerts
|

Structure–activity relationship studies on vitamin D-based selective SREBP/SCAP inhibitor KK-052

Abstract: Vitamin D3 metabolites block lipid biosynthesis by promoting degradation of the complex of sterol regulatory element-binding protein (SREBP) and SREBP cleavage-activating protein (SCAP) independent of their effects on the vitamin...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…In summary, this study has shown that KK-052, obtained as a minor product by the original synthetic method, 2,4 and its m-methyl analogue 7 can be efficiently synthesized by a [3+2] cycloaddition using sodium azide and activated amides 11 and 12. KK-052 and its related analogues 2,4 exhibit significant potential as vitamin-D 3 -based SREBP inhibitors.…”
Section: Paper Synthesis Scheme 5 Synthesis Of Kk-052 and Its Analogu...mentioning
confidence: 94%
See 2 more Smart Citations
“…In summary, this study has shown that KK-052, obtained as a minor product by the original synthetic method, 2,4 and its m-methyl analogue 7 can be efficiently synthesized by a [3+2] cycloaddition using sodium azide and activated amides 11 and 12. KK-052 and its related analogues 2,4 exhibit significant potential as vitamin-D 3 -based SREBP inhibitors.…”
Section: Paper Synthesis Scheme 5 Synthesis Of Kk-052 and Its Analogu...mentioning
confidence: 94%
“…2 Its mode of action involves inducing SREBP degradation akin to that of 25-hydroxyvitamin D 3 [25(OH)D 3 ] ( 1), yet it operates independently of the vitamin D receptor (VDR) activity. [2][3][4] This distinctive attribute positions KK-052 as a promising candidate among potential therapeutics for addressing a spectrum of SREBP-associated disorders, encompassing metabolic diseases such as obesity, diabetes mellitus, dyslipidemia, hepatosteatosis, and atherosclerosis, 5 as well as certain cancer types (Figure 1). [6][7][8][9] The activation of SREBP is implicated in lipid-driven cellular stress that leads to inflammation and fibrosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The synthetic route to the (22R)-fluoro-CD-ring (11) started from carboxylic acid (31), which was readily available from the Inhoffen-Lythgoe diol in five steps [32]. This was converted to amide (30) followed by fluorination at the C22-position using NFSI in the presence of LHMDS to give the desired (22S)-fluoro-CD-ring (29) as a major product, along with (22R)-fluoro-CD-ring (33) at a ratio of 1.4:1.…”
Section: Synthesis Of (22r)-fluoro-cd-ring (11) Via Electrophilic Flu...mentioning
confidence: 99%
“…Regio-and stereo-selective fluorination of the vitamin D 3 side-chain is one of the efficient methods used to modulate biological activities, such as binding affinity to the vitamin D receptor (VDR), transactivation activity through the VDR, and metabolic stability against CYP24A1 [1]. We have reported the regio-and stereo-selective fluorination of the CD-ring side-chain starting from the Inhoffen-Lythgoe diol (1) and constructed C26,27-fluoro-CD-rings (2-4) [2,3], C24-fluoro-CD-rings (5-7) [4,5], C23-fluoro-CD-rings (8-10) [6,7], and C22-fluoro-CD-rings (11)(12)(13) [8] (Figure 1) to create a chemical library of side-chain fluorovitamin D 3 analogues using a convergent method (Scheme 1) [9][10][11].…”
Section: Introductionmentioning
confidence: 99%